Formulation and Development of Fast Dissolving Tablet of Methanolic Extract of Some Traditionally Used Medicinal Plants for Arthritis - Tiwari, Om Prakash (International Journal of Pharmaceutical & Biological Archive, 2017)
Aim: The aim of the study is to formulate fast dissolving tablet of Methanolic Extract of Some Traditionally Used Medicinal Plants for Arthritis. Material & Methods: Fast dissolving tablet of methanolic extract of selected medicinal plants were prepared by using Crospovidone & Î²-cyclodextrin by kneading methods. Various physicochemical parameter i.e. angle of repose, bulk density, tapped density; drug content, disintegration time etc were studied. Results Hardness of tablets was between 3.2-3.7kg/cm2 for all the formulations. Friability was found in between 0.62â€0.69%. The friability value below 1% was an indication of good mechanical resistance of the tablet. The drug: content was found to be 98.18â€ 102.50% which was within the acceptable limits. Formulations F1, F4 and F7 which contains 3% super disintegrates releases 97.43%, 91.00% and 93.75% drug respectively at the end of 60 min. Conclusion: The prepared herbal fast dissolving tablets shows good disintegration property and dissolution rate. The comparative study of several superdisintegrants yielded a conclusion that Crospovidone at 3% concentration are suitable for the preparation of Herbal fast dissolving tablets which will satisfy all the criteria and official limits.